A Study on Creating Awareness of Adverse Drug Reactions in Community Pharmacists in Bangalore - Nagaraju, Kiran; K Satheesh, Vanaja; Shankar, Uday; Banu, Reshma (Indian Journal of Pharmacy Practice)
Background: Drug related effects may lead to hospitalization, patient suffering and economic burden. Adverse Drug Reaction (ADR) monitoring and reporting system helps in detection and prevention of reoccurrence of some common and also rarest adverse drug reactions. The objective of this study was to create awareness among the selected community pharmacists and to improve their level of understanding about monitoring and reporting of adverse drug reactions to the pharmacovigilance centre around the facility. Method: The resent prospective study was conducted in hundred community pharmacists (chain & private pharmacies) for a period of nine months in and around Bangalore city. The aim of our study was to create awareness in select community pharmacists about the adverse drug reactions by presenting visual presentation, displaying awareness posters at each pharmacies and distribution of yellow cards. Results: All the 100 respondents showed 100% response about the knowledge of ADRs, where to obtain the ADR forms and reporting of ADRs. 99% of the respondents became aware of reporting ADRs. 96% of respondents were aware that reporting of ADRs is an integral part of pharmaceutical care. Voluntary reporting of ADRs is agreed by 90% of the respondents. Only 8% of the respondents had received reports of ADRs from the patients and only 1% of respondents had reported an ADR. Hence, educating and training the pharmacists about the program was an important element which will improve and motivate community pharmacists to participate in reporting ADRs. Conclusion: The study reveals that awareness showed a positive response in improving the knowledge about ADRs. Well trained pharmacists in the area of ADR detection, reporting and monitoring will prove to be an asset in providing better patient care. Several approaches like continuing medical education (CME), training programmes, seminars and conferences adopted by the regulatory authorities would stimulate and become mandatory to the community pharmacists to be an integral part of reporting in ADR.
Keywords: Awareness poster; ADR; Creating awareness; Questionnaire on ADR; Visual presentation; Yellow cards